Psychotic experiences, emotion regulation, and suicidal ideation among Chilean adolescents in the general population - Wastler, Heather M.; Núñez, Daniel (Frontiers in Psychiatry, 2022)
Psychotic experiences are associated with increased risk for suicide. Despite this well-established finding, very little is known about factors that contribute to this relationship. The current study investigated the relationship between psychotic experiences, emotion regulation, and suicidal ideation among 1,590 Chilean adolescents in the general population. Participants completed self-report measures of psychotic experiences (Community Assessment of Psychic Experiences), emotion regulation (Emotion Regulation Questionnaire), depression (Patient Health Quesionnaire-9), and suicidal ideation (Columbia Suicide Severity Rating Scale). Statistical analyses included Mann–Whitney U tests, point-biserial correlations, logistic regression, and moderation analyses. Results suggest that paranoid ideation, bizarre experiences, and perceptual abnormalities were moderately associated with suicidal ideation. Additionally, greater expressive suppression and cognitive reappraisal were associated with suicidal ideation. Results from the logistic regression indicate that paranoid ideation, perceptual abnormalities, and expressive suppression have the strongest relationship with suicidal ideation, even when controlling for depression and relevant demographic variables. Additionally, paranoid ideation interacted with expressive suppression to predict suicidal ideation, with expressive suppression having the strongest relationship with suicidal ideation when paranoid ideation was low to moderate. Taken together, these findings support the broader literature suggesting that emotion regulation might be a transdiagnostic risk factor for suicidal ideation. Additional longitudinal research is needed to examine whether expressive suppression and other maladaptive emotion regulation strategies serve as a mechanism for suicidal ideation both in the general population and among individuals with psychotic experiences.